Human papillomavirus E2 proteins suppress innate antiviral signaling pathways - Li, Jin-Xin; Zhang, Jing; Li, Cheng-Hao; Zhang, Qing; Kong, Beihua; Wang, Pei-Hui (Frontiers in Immunology, 2025)
Human papillomavirus (HPV) is a major cause of cancers and benign lesions. High-risk (HR) types, including HPV16 and HPV18, are strongly implicated in cervical and other malignancies, while low-risk (LR) types, such as HPV11, are predominantly associated with benign conditions. Although the immune evasion of HPV oncoproteins E6 and E7 are extensively studied, the immunomodulatory functions of the E2 protein remain poorly underexplored. This study elucidates the role of HPV11 and HPV16 E2 proteins in modulating innate immune responses, focusing on their interaction with key innate antiviral signaling pathways. We demonstrate that HPV11 and HPV16 E2 proteins effectively suppress the activation of pivotal antiviral signaling pathways, including RIG-I/MDA5-MAVS, TLR3-TRIF, cGAS-STING, and JAK-STAT. Mechanistic analyses reveal that E2 proteins interact with the core components of type I interferon (IFN)-inducing pathways, inhibiting IRF3 phosphorylation and nuclear translocation, thereby attenuating IFN expression. Additionally, E2 disrupts the JAK-STAT signaling cascade by preventing the assembly of the ISGF3 complex, comprising STAT1, STAT2, and IRF9, ultimately inhibiting the transcription of interferon-stimulated genes (ISGs). These findings underscore the broader immunosuppressive role of HPV E2 proteins, complementing the well-established immune evasion mechanisms mediated by E6 and E7. This work advances our understanding of HPV-mediated immune evasion and positions the E2 protein as a promising target for therapeutic strategies aimed at augmenting antiviral immunity in HPV-associated diseases.